1957
DOI: 10.1084/jem.105.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Tubercle Bacillus-Monocyte Relationship

Abstract: Despite intensive research on tuberculosis and the tubercle bacillus, the important and basic problems of virulence and resistance remain a challenge.Studies of acquired immunity have revolved around the relative importance of humoral and cellular factors. As previously indicated (1), valid conclusions concerning the role of cells in acquired immunity against tuberculosis require analyses of bacterium-cell relationships during periods when the in dtro cell populations show no change in cell numbers. Under such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1957
1957
1988
1988

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 15 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…When considered in itself, this observation would appear to indicate that the cellular resistance induced in rabbits by immunization with BCG was non-specific in nature. At the same time, however, there seemed to be some element of specificity in this type of resistance (2), for the histiocytes of BCG-immunized animals failed to resist necrotization by other facultative intracellular parasites such as salmonellae. Since our earlier investigations (3) have shown that Brucdla-immune histiocytes (from rabbits immunized with Brucdla mditcnsis) also exhibited resistance against both Br~dla and myco-bacteria, it seemed reasonable to analyze more closely the question of specificity of cellular resistance by comparing the behavior of Brucelta-immune histiocytes with that of BCG-immune histiocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When considered in itself, this observation would appear to indicate that the cellular resistance induced in rabbits by immunization with BCG was non-specific in nature. At the same time, however, there seemed to be some element of specificity in this type of resistance (2), for the histiocytes of BCG-immunized animals failed to resist necrotization by other facultative intracellular parasites such as salmonellae. Since our earlier investigations (3) have shown that Brucdla-immune histiocytes (from rabbits immunized with Brucdla mditcnsis) also exhibited resistance against both Br~dla and myco-bacteria, it seemed reasonable to analyze more closely the question of specificity of cellular resistance by comparing the behavior of Brucelta-immune histiocytes with that of BCG-immune histiocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed descriptions of procedures and materials used in these studies have been described in earlier reports (1)(2)(3)(4)(5)(6) and are therefore briefly described herein.…”
Section: Methodsmentioning
confidence: 99%
“…While there is no definitive information on the mechanism of resistance to tuberculosis, certain observations (6,7,11,12) have suggested that it may be partially dependent upon cellular and humoral factors. At the "tissue culture level" it was found that immune monocytes from BCG-immunized animals could be protected against the necrot/zing action of virulent tubercle bacilli by introduction of immune sera derived from animals immunized with either tubercle bacilli or agents totally unrelated to Mycobacteriura (7).…”
Section: Discussionmentioning
confidence: 99%
“…At the "tissue culture level" it was found that immune monocytes from BCG-immunized animals could be protected against the necrot/zing action of virulent tubercle bacilli by introduction of immune sera derived from animals immunized with either tubercle bacilli or agents totally unrelated to Mycobacteriura (7). As reported herein, the seemingly non-specific activity of immune sera was further substantiated by the observations that globulin derived from immune sera failed to protect immune monocytes against virulent bacilli and absorption of immune sera with homologous or closely related antigens did not remove the protective serum factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation